The Relationship Between Maternal Domestic Violence and Infant and Toddlers’ Emotional Regulation: Highlighting the Need for Preventive Services - Geyer, Chelsea (Journal of interpersonal violence, 2021)
In an effort to further understand the impact of domestic violence (DV) on infant and toddlers’ development, this research utilized data from the second cohort of National Survey of Child and Adolescent Well-Being (NSCAW II) to examine the relationship between maternal DV and infant and toddlers’ emotional regulation, and determine whether mothers’ receipt of DV services mediated this relationship. The sample was limited to children aged 0 to 3 years and included (a) infants less than 1 year old (n = 603), (b) infants 1 to less than 2 years old (n = 310), and (c) toddlers 2 to 3 years old (n = 268). Infant/toddlers’ emotional regulation was measured using mothers’ response on the How My Infant/Toddler/Child Usually Acts questionnaire. In addition, data were collected to assess whether (a) active DV was present during the time of the Child Protective Services (CPS) investigation and (b) mothers received DV services during the past year. Study research questions were examined using a series of multiple regression analyses. Mediation was tested based on Baron and Kenny’s recommended model for establishing mediation. The mediational model was not found to be significant; however, a positive relationship existed between maternal DV and emotional regulation among infants aged less than 1 year old (β = 1.61, p = .039). There were no statistically significant relationships between DV and emotional regulation in the other age groups. These findings highlight the need to provide CPS-involved families victimized by DV with services that focus on preventing poor infant emotional regulation.